1991
DOI: 10.1101/gad.5.5.764
|View full text |Cite
|
Sign up to set email alerts
|

Secondary structure of the homeo domain of yeast alpha 2 repressor determined by NMR spectroscopy.

Abstract: The yeast a2 protein is a regulator of cell type in Saccharomyces cerevisiae. It represses transcription of a set of target genes by binding to an operator located upstream of each of these genes. The c~2 protein shares weak sequence similarity with members of the homeo domain family; the homeo domain is a 60-amino-acid segment found in many eukaryotic transcriptional regulators. In this paper we address the question of whether ~2 is structurally related to prototypical members of the homeo domain family. We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
4
43
0
1
Order By: Relevance
“…The homeo domain is part of the carboxy-terminal domain, and NMR and crystallography experiments have shown that this region forms three a-helices that pack into a tight bundle (Phillips et al 1991;Wolberger et al 1991). A sketch of the a2 homeo domain bound to its DNA site is shown in Figure 1.…”
Section: Point Mutations In the Homeo Domain Of A2 Reduce The Level Omentioning
confidence: 99%
See 1 more Smart Citation
“…The homeo domain is part of the carboxy-terminal domain, and NMR and crystallography experiments have shown that this region forms three a-helices that pack into a tight bundle (Phillips et al 1991;Wolberger et al 1991). A sketch of the a2 homeo domain bound to its DNA site is shown in Figure 1.…”
Section: Point Mutations In the Homeo Domain Of A2 Reduce The Level Omentioning
confidence: 99%
“…Homeo domain proteins have now been found in nearly all eukaryotic organisms, ranging from yeast to humans, and several hundred members of this DNA-binding family are known (for review, see Scott et al 1989;Hayashi and Scott 1990;Wuthrich and Gehring 1992}. The structures of five different homeo domains, including that of a2, have been determined by nuclear magnetic resonance (NMR) spectroscopy or X-ray crystallography (Qian et al 1989;Kissinger et al 1990;Otting et al 1990;Phillips et al 1991;Wolberger et al 1991;Billeter et al 1993;Ceska et al 1993;Leiting et al 1993;Klemm et al 1994). Despite limited sequence identity among these homeo domains, they adopt nearly the same conformation.…”
mentioning
confidence: 99%
“…The nearly superimposable crystal structures of Engrailed and MAT α2 homeodomains show helix three almost at right angles to the DNA, and nestled in the major groove (Kissinger et al, 1990;Phillips et al, 1991;Wolberger et al, 1991). Four helix three residues (47, 50, 51 and 54) have an opportunity to contact the base pairs in the major groove.…”
Section: Specificity Determinants In Homeodomainsmentioning
confidence: 99%
“…In the MAT α2 structure, the long side chain of arginine 54 reaches back to make contact with the base pairs (Phillips et al, 1991), but in Engrailed this position is occupied by alanine whose short side chain does not participate in these interactions. Additionally, this position is not conserved among our sequences.…”
Section: Specificity Determinants In Homeodomainsmentioning
confidence: 99%
“…Flexible regions adjacent to the N terminus and C terminus of the ␣2 homeodomain are required for interaction with the Mcm1 and a1 cofactors, respectively (26, 40 -44). The three-dimensional structure of the ␣2 homeodomain has been determined by NMR and x-ray crystallography studies (42,45,46). Although there is only 27% sequence identity between the ␣2 and Drosophila engrailed homeodomains, their overall structures are very similar (46,47).…”
mentioning
confidence: 99%